Imaging of odontogenic sinusitis. Issue 7 (July 2019) - Whyte, A.; Boeddinghaus, R.
Abstract : The aetiological relationship between dental disease and procedures and mucosal disease within the maxillary sinus has received extensive attention in the recent otolaryngological and dental literature. In contrast, the concept of an odontogenic cause for sinusitis is not well appreciated by radiologists. Review of the maxillary dentition, the alveolar process, and the relationship of the tooth roots to the floor of the maxillary sinus should be an integral part of interpretation of imaging of the paranasal sinuses. The pathogenesis, clinical presentation, and imaging features of rhinogenic and odontogenic sinusitis are discussed and compared. Clinical definitions of rhinosinusitis are explained and the huge impact on healthcare of this disease is briefly discussed. Periapical inflammatory lesions, post-extraction oroantral communication, and procedures used to augment the alveolar process prior to placement of dental implants are the commonest causes of odontogenic sinusitis. Current estimates are that an odontogenic cause for maxillary sinusitis is present in 25–40% of cases. The incidence of odontogenic sinusitis is rising, extension outside the maxillary sinus is common, and the diagnosis is often delayed, resulting in inappropriate and failed treatment. Differentiation of rhinological and odontogenic causes of sinusitis is usually difficult on clinical grounds and imaging plays a key role in the distinction. Highlights: The root apices of the maxillary molar and second premolar teeth are intimately related to the maxillary sinuses. Mucosal thickening in the inferior aspect of the maxillary sinus is usually dental in aetiology. OS accounts for up to 40% of sinusitis involving the maxillary sinus. OS is most commonly due to periapical sepsis or is iatrogenic in nature. Review of the maxillary teeth should be an integral part of the reporting checklist.